STUDI EKSPERIMEN KUAT LEKAT MORTAR BIASA PADA PASANGAN BETON RINGAN AERASI - Yulianto Hendra, Imam Muchoyar (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2014)
This study aims to determine the capacity of shear strength aerated lightweight concrete (AAC)with ordinary mortar and knowing the effective of mortar mix of aerated lightweight concrete.Aerated lightweight concrete is composed of a pair of aerated lightweight concrete usingordinary mortar binder. This research uses experimental study approach with 1PC:4 Ps; 1PC:5PS; 1PC: 6PS in proportion mix. The test object pair aerated lightweight concrete "Z" made oftwo pieces of lightweight measuring 10 x 10 x 20 cm. The data analysis used descriptivequantitative. The test result showed that the compressive strength and tensile strength of mortarwith 1PC:4PS; 1PC:5PS are 6,526MPa and 0,075MPa. The damage crack pattern is interfacefailure; and effective composition of mortar is 1PC: 4Ps in proportion mix.Keywords: Autoclaved Aerated Concrete, mortar.